1973
DOI: 10.1128/iai.8.6.952-961.1973
|View full text |Cite
|
Sign up to set email alerts
|

Filamentous Capsulated Streptococci from the Human Respiratory Tract I. Antigenic Attributes of Provisional Capsular Type 83 and Its Relationship to Streptococci of So-Called Group M

Abstract: Two immunologically reactive polysaccharides have been isolated from the cell walls and from culture filtrates of a filamentous alpha-hemolytic streptococcus provisionally designated capsular type 83. Both polysaccharides were purified by diethylaminoethyl-cellulose chromatography. Analysis indicates that the capsular polysaccharide consists of galactose and phosphorus, whereas the cell wall polysaccharide contains galactosamine, glucosamine, glucose, and phosphorus. On the basis of immunochemical experiments,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

1973
1973
1990
1990

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…DISCUSSION The cell wall polysaccharides extracted from streptococcal walls with 0.5 N HCI (pH 2) at 100 C (19), formamide at 170 C (11) and Streptomyces albus enzyme (21) have been found to be composed of rhamnose, glucose, galactose, N-acetylglucosamine, and N-acetylgalactosamine in various combinations (29). We have fractionated the cell wall polysaccharide(s) of S. sanguis into at least four fractions to the purity of 95% or more as judged by polyacrylamide gel (15,16,17) reported that the cell wall polysaccharides of three filamentous streptococci isolated from a human respiratory tract contained phosphate in addition to glucosamine, galactosamine, and glucose, but the presence of glycerol was not reported. Recently (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…DISCUSSION The cell wall polysaccharides extracted from streptococcal walls with 0.5 N HCI (pH 2) at 100 C (19), formamide at 170 C (11) and Streptomyces albus enzyme (21) have been found to be composed of rhamnose, glucose, galactose, N-acetylglucosamine, and N-acetylgalactosamine in various combinations (29). We have fractionated the cell wall polysaccharide(s) of S. sanguis into at least four fractions to the purity of 95% or more as judged by polyacrylamide gel (15,16,17) reported that the cell wall polysaccharides of three filamentous streptococci isolated from a human respiratory tract contained phosphate in addition to glucosamine, galactosamine, and glucose, but the presence of glycerol was not reported. Recently (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Preliminary evidence has suggested that the cross-reacting cell wall antigens of these filamentous streptococci have similar immunological features and might represent, therefore, a common group-specific antigen. Previous studies have shown that the cell wall antigen of the prototypic strain of filamentous streptococcal capsular type 83 contains galactosamine, glucosamine, glucose, and phosphorus (16). Although an immunological relationship was demonstrated between this antigen and pneumococcal C polysaccharide, the immunochemical basis for the cross-reactivity was not defined.…”
Section: Resultsmentioning
confidence: 97%
“…Earlier studies have drawn attention to the immunological cross-reactivity between the C. capsular polysaccharide of pneumococcus (5) and a variety of strains of capsulated filamentous alphaand nonhemolytic streptococci of the human respiratory tract (2,16). Such an immunological relationship is consistent with the observation that the cell walls of pneumococcus and of a filamentous streptococcus studied previously have in common certain chemical constituents, namely galactosamine, glucosamine, glucose, phosphate, and several amino acids (16). In the following experiments, the immunochemical basis for the cross-reactivity between the cell walls of pneumococcus and of a filamentous alpha-hemolytic streptococcus has been investigated in greater detail.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found previously that many strains of alphaand nonhemolytic streptococci isolated from human respiratory secretions produce type-specific capsular substances (2,11). Extensive immunological studies of a collection of filamentous morphological variants giving rise to rugose colonies on the surface of agar plates have revealed the existence of at least 30 capsular serotypes.…”
mentioning
confidence: 99%